COGNITIVE LEVEL OF CONSUMERS’ KNOWLEDGE IN THE CASE OF A FEW FOOD PRODUCTS - Robert Sandor Szucs (European Scientific Journal, ESJ, 2014)
Nowadays, the number of stimuli reaching the consumers is underdrastic growth. At the same time, consumers are not able to or willing toprocess this amount of information. In spite of the educational level,informative campaigns and publications, the consumers‘ level of knowledgeremains low concerning the composition of food products. On the basis of aresearch carried out in 2013, in Hungary and involving 1,150 individuals, wecan state that consumers are not aware of the extent of carbohydrates andenergy contained in their food products. It is the responsibility of consumerprotection to work out a signalling for food products that is easy to beprocessed and can be immediately understood by the consumers. Such aninitiative could be the comprehensive and mandatory introduction of the―traffic light system‖.